The Politics of Critique - Fredrik Portin (Lychnos, 2018)
In the article I argue, through the sociologist and philosopher Bruno Latour’s works, that critique is a political endeavour. The first part of the paper analyses Latour’s description of politics as re-presentation and thereafter I argue that the necessity for re-presentative politics makes critique an essential part of politics. In the second part, an analysis of Latour’s argument that the scholar is a political actor is carried out. The conclusion is, that to the extent that the scholar expresses critique, he or she will be engaged in politics. Finally, I analyse what, according to Latour, constitutes good and bad critique from a political perspective.